Pengaruh Strategi Belajar Tuntas Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti - Andreas Fernando; Dorlan Naibaho; Tiurma Baras (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The aim of this research is to determine the positive and significant influence of comprehensive learning strategies on the learning outcomes of Christian Religious Education and Character Education for Class VIII Students at SMP Negeri 2 Muara for the 2022/2023 Academic Year. The method used in this research is quantitative descriptive inferential statistics. The population is all class VIII students of SMP Negeri 2 Muara for the 2022/2023 academic year, totaling 104 people and a sample of 36 people was determined, namely 35% of the population. Data was collected using a positive closed questionnaire with 20 items. The results of data analysis show that there is a positive and significant influence of the complete learning strategy on the learning outcomes of Christian Religious Education and Characteristics of Class VIII Students of SMP Negeri 2 Muara for the 2022/2023 Academic Year: 1) Test the analysis requirements: a) test the positive relationship to obtain a value rxy = 0.512 > rtable(=0.05,n=36) = 0.329, thus it is known that there is a positive relationship between variable .05,dk=n-2=34)=2.042, thus there is a significant relationship between variable X. b) Regression coefficient of determination test (r2) = 26.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable, namely 9.50 > 1.51. Thus, Ha is accepted and H0 is rejected.